Extremists into Truth-tellers: Information Aggregation under Asymmetric Preferences - Jean-Philippe Bonardi; Olivier Cadot; Lionel Cottier (Fondation pour les études et recherches sur le développement international (FERDI), 2016)
We set up a model of costly information production between two lobbies, a firm and a consumer group, competing for influence over an imperfectly informed but benevolent government. The government is endowed with a parametric amount of information and chooses the best policy from a finite, countable feasible set given the information available (its own and that forwarded by lobbies). Lobbies have asymmetric preferences, the firm being a "high-stakes" player with relatively extreme preferences and the consumer group a "low-stakes" player with preferences more aligned with the government's. We show that lobbies spend too much on information production in any Nash equilibrium despite a timing-game structure in which the lobbies are free to choose the order of play. We also show that in some parameter configurations, the firm insures against a consumer win by forwarding unbiased information to the government, in spite of its own extreme preferences and high stakes. The resulting informational rent enables the government to adopt moderate policies aligned with its own (i.e. societal) preferences, suggesting a new way in which lobby competition can produce good policies even when the government is imperfectly informed.
Keywords: H4; K0; P1; D72; F13; 330; Game theory; lobbying model; imperfect information; timing game